Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan KRL Commuter Line di Jabodetabek - Aulia Syafitri; Musthafa Kamil (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
The number of Commuter Line KRL passengers in Jabodetabek has not returned to pre-Covid-19 levels, despite an increase from 2022. In 2019, the number of passengers reached 336,274,343 or 13% higher than in 2023. This decline is not only caused by the pandemic, but also by customer dissatisfaction with PT KCI services, such as facilities and service quality. This study aims to determine the effect of facilities and service quality on KRL Commuter Line customer satisfaction in Jabodetabek. This research uses descriptive methods based on quantitative data. The population of this study were users of KRL Commuter Line transportation services in Jabodetabek with a sample of 100 respondents using purposive sampling technique. Data collection methods using questionnaires and documentation studies. The data analysis technique used is validity, reliability, classical assumption test, multiple linear regression test, hypothesis testing, namely t test, f test and partial and simultaneous determination coefficient using SPSS version 25. The results showed that partially the facility variable had a significant effect on customer satisfaction and the service quality variable also had a significant effect on customer satisfaction. Then simultaneously the facility variables and service quality have a significant effect on customer satisfaction.